2018
DOI: 10.1111/ejn.13822
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic ketamine on hippocampal cross‐frequency coupling: implications for schizophrenia pathophysiology

Abstract: Disrupted neuronal oscillations have been identified as a potentially important biomarker for the perceptual and cognitive symptoms of schizophrenia. Emerging evidences suggest that interactions between different frequency bands, cross-frequency coupling (CFC), serve an important role in integrating sensory and cognitive information and may contribute to disease pathophysiology. In this study, we investigated the effects of 14-day consecutive administration of ketamine (30 mg/kg i.p.) vs. saline on alterations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 73 publications
1
13
0
Order By: Relevance
“…In freely moving animals, it was shown that acute ketamine can increase cross-frequency coupling between gamma activity and theta oscillations in the hippocampus of rats 16 . Chronic ketamine treatment also causes long-term alterations on theta-gamma CFC depending on the behavioral state 64 . Theta oscillations are prominent during exploratory activity 65 and theta-gamma CFC has been related to working memory and memory consolidation mechanisms [66][67][68] .…”
Section: Discussionmentioning
confidence: 99%
“…In freely moving animals, it was shown that acute ketamine can increase cross-frequency coupling between gamma activity and theta oscillations in the hippocampus of rats 16 . Chronic ketamine treatment also causes long-term alterations on theta-gamma CFC depending on the behavioral state 64 . Theta oscillations are prominent during exploratory activity 65 and theta-gamma CFC has been related to working memory and memory consolidation mechanisms [66][67][68] .…”
Section: Discussionmentioning
confidence: 99%
“…Michaels et al . () document the changes to cross‐frequency coupling (CFC) and behavior in a rodent schizophrenia model (chronic ketamine administration) to start looking into the potential relevance of CFC in the pathophysiology of the psychoses. In a provocative piece, Klimesch () explores the frequency architecture of brain oscillations, specifically detailing cross‐frequency coupling principles, and extending this notion to mind‐body interactions where he asks if oscillatory‐like motor activity is simply another version of communication across systems that is governed by coupled oscillators.…”
Section: The Multilayered Interactions Of Neural Oscillationsmentioning
confidence: 99%
“…A similar need for additional studies surrounds the preclinical observations of altered gamma-band PAC in mouse models relevant to ASD. Several recent preclinical studies report alterations to the strength of task-related gammaband PAC in murine models relevant to ASD (Cao et al, 2018;Michaels et al, 2018;Radwan et al, 2016), but the changes are complex and potentially not consistent. Separately RS theta to high-gamma PAC appears decreased in mice that have a genetic insult relevant to ASD (Port et al, 2017b).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated murine models of relevance to ASD for alterations to the strength (amplitude) of task-related gamma-band PAC. Although these studies do report altered strength of gamma-band PAC in these mice as compared with either WT (Radwan et al, 2016) or before pharmacological insult (Michaels et al, 2018), the changes are complex and potentially inconsistent. Spontaneous RS gamma-band PAC has also been examined in a mouse model relevant to ASD, although the exact interpretation of such a ''resting'' period in mice is frequently disputed.…”
Section: Introductionmentioning
confidence: 94%